'AKAR' DAN 'LUKU' DI KOTA, TRAKTOR DI DESA Kriya Kayu Rastik dalam Konteks Valorisasi, Partikularisasi Gaya ITidup, dan Perubahan Sosio-Kultural Masyarakat Kontemporer - Sri Krisnanto (Ars: Jurnal Seni Rupa dan Desain, 2007)
This article discusses the development o f rustic craps nowadays. Rustic craft in this articlemeans a work o f craft that is "made'' o f natural materials, such as roots, and ru ral-folk-crafts, fo r example,"lesutig" and "luku " (plough). These kinds o f crafts are becoming popular among the middle-to-high classcommunities in the cities. The crafts function ils a signifier in gaining social status which differentiate c,certain class with other classes, and also fulfil their needs o f a different life style and their aesthetkal value.Such a condition increases a valorization o f rustic craft in economical and symbolic sense, but, at the sametime, creates an ironic condition especially in the context o f sccio-cultural shifting in a rural area. Thevillagers, especially the farmers, are withdrawn from their socio cultural base since they become unfamiliarwith their fvlk-funitiunul-crufts.Key ivords: life style, craft, rustic craft, discourse, valorization.